Discrepancy index, treatment complexity index and objective Grading system: correlation between parameters, indices and implications for treatment - Syed Mohamed Alizae Marny Fadzlin; Yusop Nurul Naziha; Rasidi Nurul Sabryna; Ashari Asma; Cheen Amy Liew Kia (Sciendo, 2024)
An assessment of orthodontic treatment duration and results allows for measurable outcomes, goal-setting, and the establishment of patient management standards. It is important information that can be utilised for educational purposes in an orthodontic postgraduate program. The aim of this study was to determine correlations of the parameters within and between the Objective Grading System (OGS), Discrepancy Index (DI) and Treatment Complexity Index (TCI) and identify those factors associated with treatment outcomes and duration.